Axionic Dark Matter in a Bi-Metric Universe - Mendez-Ferrada, F; Maldonado-Salazar, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
We study the evolution and production of axion dark matter in a universe model with two scale factors corresponding to different patches of the universe. The interaction between patches is described through a deformed Poisson bracket structure. The first part of the present paper is devoted to a review of the results reported in previous works concerning the study of dark matter as WIMPs and FIMPs. The new results concerning axionic dark matter in this bi-metric scenario show that different values of the deformation parameter (Formula presented.) allow values of masses and misalignment angles forbidden in standard cosmology. The present model can also be considered a different type of nonstandard cosmology consistent with previously reported results. © 2023 by the authors.